Polyhydroxyalkanoate bamboo powder composite material and preparation method thereof

By developing polyhydroxy fatty acid ester bamboo powder composite materials, the problem of existing biodegradable materials not being fully environmentally friendly and rapidly degraded during use is solved, and the material performance improvement and cost reduction are achieved, while maintaining biodegradability.

CN119899538APending Publication Date: 2025-04-29HUBEI WEIQI BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202411911791.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing biodegradable materials fail to achieve complete environmental protection and rapid degradation during their life cycle during use, and non-degradable plastics need to be added during the modification process to improve compatibility, which violates environmental protection standards.

Method used

Develop a polyhydroxy fatty acid ester bamboo powder composite material to improve the mechanical properties and processing properties of the material through formulation design, reduce the amount of polyhydroxy fatty acid ester, maintain biodegradability, and reduce production costs.

Benefits of technology

The mechanical properties and processing properties of composite materials are improved, the disadvantage of slow crystallization of polyhydroxy fatty acid ester is overcome, the biodegradability is maintained, and the cost is greatly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206265580000101
    Figure BDA0005206265580000101
  • Figure BDA0005206265580000111
    Figure BDA0005206265580000111
  • Figure BDA0005206265580000151
    Figure BDA0005206265580000151
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, in particular to a polyhydroxyalkanoate bamboo powder composite material and a preparation method thereof. The composite material comprises the following raw materials in percentage by weight: 30-45% of polyhydroxyalkanoate, 30-45% of bamboo powder, 1-15% of filler, 0.1-5% of a coupling agent, 0.1-1% of a chain extender, 0.1-5% of a lubricant, 0.1-5% of a heat stabilizer, 0.1-2% of an anti-hydrolysis agent and 0.1-2% of an antioxidant, wherein the polyhydroxyalkanoate is prepared from PHB (Polyhydroxyalkanoate) and P3HB4HB (Polyhydroxyalkanoate). According to the invention, the polyhydroxyalkanoate and the bamboo powder are blended, so that the mechanical property and the processability of the composite material are improved through formula design, the comprehensive performance of the polyhydroxyalkanoate composite material is improved, and the defect of low crystallization speed of the polyhydroxyalkanoate is overcome; meanwhile, the biodegradability of the polyhydroxyalkanoate is kept, the dosage of the polyhydroxyalkanoate is reduced, and the cost is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a polyhydroxyalkanoate bamboo powder composite material and a preparation method thereof. Background Art

[0002] With the rapid economic development, people's living standards are improving day by day, and people have higher and higher requirements for environmental quality. However, the global application of non-degradable disposable plastics has aggravated the white pollution of the human living environment. Common biodegradable materials at home and abroad, such as polylactic acid (PLA), polycaprolactone (PCL), polybutylene adipate / terephthalate (PBAT), polybutylene succinate (PBS) and polyhydroxyalkanoates (PHA), have developed well, their performance has been continuously improved, and their applications have become more and more extensive, such as daily necessities, medical fields, packaging fields, catering fields, etc. However, because some biodegradable materials are derived from petroleum-based materials such as PBS and PBAT, some degradation requires specific industrial composting conditions to degrade, such as PLA. Therefore, except for PHA, other materials cannot achieve complete environmental protection and rapid degradation during their life cycle when used.

[0003] Bamboo is a widely distributed, easily available plant with certain economic value. In the prior art, bamboo is ground into bamboo powder by physical means, and adding it to polylactic acid can not only improve the mechanical properties of polylactic acid but also reduce the cost of the material. At present, the research on degradable bamboo powder composite materials mainly focuses on blended materials such as PLA, PBS and PBAT. For example, Chinese patent CN106832831A is modified by adding bamboo powder to polylactic acid. However, in order to increase the compatibility between bamboo powder and polylactic acid during the modification process, polyethylene non-degradable plastic products are added, which damages the biodegradable properties of polylactic acid and does not comply with the national standard "GB / T 41010-2021 Biodegradable Plastics and Products Degradation Performance and Labeling Requirements".

[0004] Currently, there is little research on bamboo powder composites using polyhydroxyalkanoates, so there is an urgent need to develop an environmentally friendly polyhydroxyalkanoate bamboo powder composite material with good performance and biodegradability in the natural environment. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a polyhydroxyalkanoate bamboo powder composite material, improve the performance of the composite material, reduce the amount of polyhydroxyalkanoate used, reduce the production cost of the composite material, and meet the needs of industrial production.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The present application provides a polyhydroxyalkanoate bamboo powder composite material, comprising the following raw materials in weight percentage: 30-45% polyhydroxyalkanoate, 30-45% bamboo powder, 1-15% filler, 0.1-5% coupling agent, 0.1-1% chain extender, 0.1-5% lubricant, 0.1-5% heat stabilizer, 0.1-2% anti-hydrolysis agent and 0.1-2% antioxidant; wherein the polyhydroxyalkanoate comprises PHB and P3HB4HB.

[0008] In some embodiments of the present application, based on the weight of the polyhydroxyalkanoate bamboo powder composite material as 100%, the polyhydroxyalkanoate includes 20-40% PHB and 5-20% P3HB4HB, preferably the polyhydroxyalkanoate includes 20-30% PHB and 5-20% P3HB4HB; preferably, the molar content of 4HB in the P3HB4HB is 5-20%; more preferably, the weight average molecular weight of the PHB is 50-90w, and the weight average molecular weight of the P3HB4HB is 50-90w.

[0009] In some embodiments of the present application, the polyhydroxyalkanoate is 40-45%; and / or, the bamboo powder is 30-40%.

[0010] In some embodiments of the present application, the filler is 10-15%; and / or,

[0011] The coupling agent is 1-5%, preferably 1-2%; and / or,

[0012] The chain extender is 0.5-1%; and / or,

[0013] The lubricant is 1.5-5%, preferably 1.5-3%; and / or,

[0014] The thermal stabilizer is 0.5-5%, preferably 1-5%; and / or,

[0015] The anti-hydrolysis agent is 0.5-2%; and / or,

[0016] The antioxidant is 0.5-2%.

[0017] In some embodiments of the present application, the coupling agent includes one or more of a maleic anhydride coupling agent, a titanate coupling agent, an aluminate coupling agent and a silane coupling agent; preferably a titanate coupling agent and a silane coupling agent, more preferably a mass ratio of the titanate coupling agent to the silane coupling agent is 0.5-3:0.5-2, preferably 0.5-1:0.5-1.

[0018] In some embodiments of the present application, the chain extender includes one or more of an epoxy functional group chain extender, an oxazoline type chain extender, an isocyanate chain extender and a peroxide; preferably an epoxy functional group chain extender.

[0019] In some embodiments of the present application, the lubricant includes low molecular weight fully degradable polyester and / or low molecular weight polyhydroxyalkanoate.

[0020] In some embodiments of the present application, the heat stabilizer includes one or more of calcium stearate, zinc stearate, nanocellulose, nano-montmorillonite and fumed silica, preferably calcium stearate and / or zinc stearate; and / or,

[0021] The anti-hydrolysis agent includes carbodiimides; and / or,

[0022] The filler comprises one or more combinations of talc, calcium carbonate, whiskers or kaolin, preferably calcium carbonate and talc; and / or

[0023] The antioxidant includes one or more of hindered phenols, phosphates, phosphites and aromatic amines, preferably hindered phenols and / or phosphates.

[0024] The present application also provides a method for preparing the above-mentioned composite material, which comprises the following steps:

[0025] (1) mixing, heating and mixing the raw materials, and cooling to obtain a mixed material;

[0026] (2) Granulation: granulating the mixed material obtained in step (1).

[0027] In some embodiments of the present application, the heating temperature in step (1) is 100-120° C., and the preferred mixing time is 20-30 min.

[0028] In some embodiments of the present application, the granulation in step (2) comprises adding the mixture obtained in step (1) into a twin-screw extruder for melt blending and extrusion granulation, preferably the extrusion temperature is 140-160°C, and more preferably the rotation speed is 200-350rpm.

[0029] In some embodiments of the present application, the preparation method further comprises the step of molding the particles obtained in step (2), preferably molding the particles obtained in step (2) by extrusion, injection molding, casting or die casting.

[0030] Beneficial effects of the present invention:

[0031] The invention adopts the blending of polyhydroxyalkanoate and bamboo powder, improves the mechanical properties and processing properties of the composite material through formula design, improves the comprehensive performance of the polyhydroxyalkanoate composite material, overcomes the disadvantage of slow crystallization speed of polyhydroxyalkanoate, maintains the biodegradability of polyhydroxyalkanoate, reduces the amount of polyhydroxyalkanoate used, and greatly reduces the cost. DETAILED DESCRIPTION

[0032] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0033] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementations", or "some specific implementations" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0034] In order to make the purpose, technical scheme and technical effect of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention is described clearly and completely. The embodiments described below are part of the embodiments of the present invention, not all of them. In combination with the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] To achieve the above object, in a specific embodiment of the present application, the present application provides a polyhydroxyalkanoate bamboo powder composite material, comprising the following components in weight percentage: 30-45% polyhydroxyalkanoate, 30-45% bamboo powder, 1-15% filler, 0.1-5% coupling agent, 0.1-1% chain extender, 0.1-5% lubricant, 0.1-5% heat stabilizer, 0.1-2% anti-hydrolysis agent and 0.1-2% antioxidant;

[0036] Wherein, the polyhydroxyalkanoates include PHB and P3HB4HB.

[0037] PHB is the abbreviation of poly 3-hydroxybutyrate, which is a homopolymer of 3-hydroxybutyric acid.

[0038] P3HB4HB is the abbreviation of poly(3-hydroxybutyrate-co-4-hydroxybutyrate), which is a polymer material formed by copolymerization of 3-hydroxybutyric acid (3HB) and 4-hydroxybutyric acid (4HB) through ester bonds, where "co" means copolymerization. P3HB4HB is the fourth generation of PHA, with excellent biodegradability, biocompatibility, optical activity, piezoelectricity and gas separation. It is biodegradable in the natural environment. After its molecules are degraded or ashed, they form carbon dioxide and water that are harmless to the soil and air. Therefore, it can be used as a biodegradable polymer to replace traditional polymers and solve the problem of difficult degradation of petroleum-based materials. However, P3HB4HB also has defects: P3HB4HB is synthesized intracellularly in bacteria without a catalyst, so its crystal nucleus density is low, the crystallization induction period is long, and the spherulite size is large; its melting point is close to the thermal decomposition temperature, which makes the processing window narrow; its thermal stability is poor and it is easy to decompose during processing; its glass transition temperature is around 0°C, it is in a highly elastic state at room temperature, and the material stability is poor.

[0039] In some embodiments of the present application, the weight average molecular weight of PHB is 500,000-900,000, and the weight average molecular weight of P3HB4HB is 500,000-900,000. Generally speaking, the larger the molecular weight, the better the thermal stability of the material. This is because the number of internal bonds in the molecules of materials with large molecular weight is greater, so the interaction force within the molecules is stronger at high temperatures and is more difficult to be destroyed. At the above molecular weight, both the material processing performance and the performance of the processed material can be met.

[0040] In some embodiments of the present application, the molar content of 4HB (4-hydroxybutyric acid) in P3HB4HB is 5-20% by comprehensive consideration of cost and material performance. 4HB can improve the elongation at break of PHA, or in layman's terms, can improve the toughness of the material. The higher the content, the stronger the toughness, and the lower the content, the stronger the rigidity.

[0041] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 35-45% of polyhydroxyalkanoate, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 35-45% of polyhydroxyalkanoate. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 30%, 35%, 40%, 41%, 42%, 43%, 44% or 45% of polyhydroxyalkanoate, or a polyhydroxyalkanoate within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0042] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 20-30% PHB, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 20%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or 40% PHB, or PHB within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0043] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 5-20% P3HB4HB, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 5%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20% P3HB4HB, or P3HB4HB within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0044] In the present application, bamboo powder is powder made by grinding bamboo.

[0045] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 30-40% bamboo powder, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 30%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, or 45% bamboo powder, or bamboo powder within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0046] In some embodiments of the present application, the chain extender includes one or more of epoxy functional group chain extender, oxazoline chain extender, isocyanate chain extender and peroxide; preferably, epoxy functional group chain extender can promote cross-linking of epoxy groups to achieve hardening of epoxy plastics. At the same time, due to the occurrence of chain extension reaction, plastic polymers with larger molecular weight can be formed, which can improve physical and chemical properties such as hardness, strength, heat resistance, chemical corrosion resistance, etc., and can also increase the toughness and flexibility of the resin.

[0047] In some embodiments of the present application, the chain extender is selected from one or more of BASF ADR 4468, BOZ (2,2-bis-(2-oxazoline), diphenylmethane diisocyanate (MDI) and dicumyl peroxide, preferably BASF ADR 4468.

[0048] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material includes 0.5-1% of a chain extender, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material includes 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1% of a chain extender, or a chain extender within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges. The addition of a chain extender improves the molecular structure of the polyhydroxyalkanoate, making its structure relatively regular and symmetrical, and significantly improving the crystallization rate.

[0049] In some embodiments of the present application, the lubricant comprises a low molecular weight fully degradable polyester and / or a low molecular weight polyhydroxyalkanoate, preferably a low molecular weight polyhydroxyalkanoate. Polymers usually have a higher viscosity after melting, and during processing, the polymer melt must produce friction with the surface of the processing machinery, and some friction is very unfavorable for the processing of polymers, and these frictions reduce the melt fluidity, and severe friction can make the film surface rough, lack of gloss or flow lines, for this reason, it is necessary to add a lubricant. Low molecular weight fully degradable polyester and / or a low molecular weight polyhydroxyalkanoate (or used in conjunction with other components) can improve lubricity, reduce friction, and reduce the purpose of interfacial adhesion performance; in addition to improving fluidity, it can also play the role of melting promoter, anti-adhesion and antistatic agent, slip agent, etc.

[0050] It should be noted that, in the present application, the low molecular weight fully degradable polyester refers to a fully degradable polyester with a weight average molecular weight of 5-10w, and the low molecular weight polyhydroxyalkanoate refers to a polyhydroxyalkanoate with a weight average molecular weight of 10-20w.

[0051] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material includes 1.5-5% of lubricant, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material includes 1.5-3% of lubricant. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material includes 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% of lubricant, or a lubricant within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0052] In some embodiments of the present application, the heat stabilizer includes one or more of calcium stearate, zinc stearate, nanocellulose, nano-montmorillonite and fumed silica.

[0053] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material includes 0.5-5% of a heat stabilizer, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material includes 1-5% of a heat stabilizer. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material includes 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% of a heat stabilizer, or a heat stabilizer within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0054] In some embodiments of the present application, the anti-hydrolysis agent includes carbodiimides.

[0055] In some embodiments of the present application, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material, the polyhydroxyalkanoate bamboo powder composite material includes 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5% or 2% of an anti-hydrolysis agent, or a heat stabilizer within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0056] In some embodiments of the present application, the filler includes one or more combinations of talc, calcium carbonate, whiskers or kaolin, preferably calcium carbonate and talc.

[0057] In some embodiments of the present application, based on the weight of the polyhydroxyalkanoate bamboo powder composite material as 100%, the polyhydroxyalkanoate bamboo powder composite material includes 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15% of filler, or filler within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0058] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 5-10% calcium carbonate, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15% calcium carbonate, or calcium carbonate within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0059] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 5-10% talc, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15% talc, or talc within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0060] In some embodiments of the present application, the coupling agent includes one or more of maleic anhydride coupling agents, titanate coupling agents, aluminate coupling agents and silane coupling agents; preferably titanate coupling agents and silane coupling agents. These two coupling agents can improve the performance of the material. Experimental verification shows that the toughness and impact strength of the material are enhanced, which is better than maleic anhydride coupling agents. Titanate coupling agents can activate fillers, increase the filling amount, reduce the amount of resin, reduce product costs, and improve processing performance and increase product gloss and material properties.

[0061] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 1-5% of a coupling agent, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 1-2% of a coupling agent. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% of a coupling agent, or a coupling agent within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0062] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 0.5-2% of a silane coupling agent, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 0.5-1% of a silane coupling agent. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5% or 2% of a silane coupling agent, or a coupling agent within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0063] In some embodiments of the present application, based on the weight of the polyhydroxyalkanoate bamboo powder composite material as 100%, the polyhydroxyalkanoate bamboo powder composite material includes 0.5-3% of a titanate coupling agent. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material includes 0.5-1% of a titanate coupling agent. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material includes 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5% or 3% of a titanate coupling agent, or a titanate coupling agent within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0064] In some embodiments of the present application, the antioxidant includes one or more of hindered phenols, phosphates, phosphites and aromatic amines; preferably hindered phenols and / or phosphates.

[0065] In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 0.5-2% antioxidant, based on 100% by weight of the polyhydroxyalkanoate bamboo powder composite material. In some embodiments of the present application, the polyhydroxyalkanoate bamboo powder composite material comprises 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5% or 2% antioxidant, or an antioxidant within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.

[0066] In a second aspect, the present application also provides a method for preparing the above-mentioned composite material, which comprises the following steps:

[0067] (1) mixing, heating and mixing the raw materials, and cooling to obtain a mixed material;

[0068] (2) Granulation: granulating the mixed material obtained in step (1).

[0069] In some embodiments of the present application, the heating temperature in step (1) is 100-120° C., and the preferred mixing time is 20-30 min.

[0070] In some embodiments of the present application, the granulation in step (2) comprises adding the mixture obtained in step (1) into a twin-screw extruder for melt blending and extrusion granulation, preferably the extrusion temperature is 145-165°C, and more preferably the rotation speed is 200-350rpm.

[0071] In some embodiments of the present application, the preparation method further comprises the step of molding the particles obtained in step (2), preferably molding the particles obtained in step (2) by extrusion, injection molding, casting or die casting.

[0072] The beneficial effects of the present invention are further illustrated by specific examples below.

[0073] The raw materials and reagents used in the present invention are all purchased from mainstream manufacturers in the market. Those without manufacturer or concentration are all analytically pure raw materials and reagents that can be routinely obtained. As long as they can play the expected role, there is no special limitation.

[0074] If no specific technology or conditions are specified in this embodiment, the process shall be carried out according to the technology or conditions described in the literature in the art or according to the product manual.

[0075] Hereinafter, the present invention will be described in more detail using examples and comparative examples, but the technical scope of the present invention is not limited to these examples. It should be noted that, unless otherwise specified, all percentages, parts, and ratios used in the present invention are based on mass.

[0076] The sources of the reagents and instruments used in the following examples are shown in Table 1.

[0077] Table 1 Raw material information used in the examples

[0078]

[0079]

[0080]

[0081] The polyhydroxyalkanoate bamboo powder composite materials in the examples and comparative examples were tested using the following method, and the results are shown in Table 2.

[0082] Melt index (melt flow rate, unit: g / 10min) is measured according to the method in GB / T 3682-2000 Determination of mass flow rate and melt volume flow rate of thermoplastic melts, wherein the test conditions are: test temperature 190°C, nominal load 2.16kg.

[0083] Tensile strength (unit: MPa), according to GB / T 1040.2-2006 Determination of tensile properties of plastics

[0084] Tensile elongation at break (%) is measured according to the method in GB / T 1040.2-2006 Determination of tensile properties of plastics Part 2: Test conditions for molding and extruded plastics.

[0085] Izod notched impact strength (unit: kJ / m 2 ), measured according to the method in GB / T 1843-2008 Determination of plastic cantilever beam notched impact strength. The sample size is 10mm×10mm×55mm, the notch type is A, and the retained width of the notch is 8mm.

[0086] Example 1

[0087] 30g of PHB, 15g of P3HB4HB (4HB molar content 10%), 40g of bamboo powder, 5g of talc, 5g of calcium carbonate, 0.5g of silane coupling agent KH550, 0.5g of titanate coupling agent TCA-KTTS, 0.5g of BASF ADR 4468, 1.5g of low molecular weight PHB, 1.0g of calcium stearate, 0.5g of anti-hydrolysis agent, and 0.5g of antioxidant CYANOX 1010 were weighed and added into a high-speed mixer for mixing for 25min, the high-speed mixer temperature was 100°C, and then cooled to room temperature, and the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, and cooled and drawn into granules. Wherein, the twin-screw processing temperature was 140-160°C, and the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0088] Example 2

[0089] 20g of PHB, 20g of P3HB4HB (4HB molar content 10%), 30g of bamboo powder, 10g of talc, 5g of calcium carbonate, 1g of silane coupling agent KH550, 1g of titanate coupling agent TCA-KTTS, 1g of BASF ADR 4468, 3g of low molecular weight PHB, 5g of zinc stearate, 2g of anti-hydrolysis agent, and 2g of antioxidant 168 were weighed and added into a high-speed mixer for mixing for 25 minutes, the temperature of the high-speed mixer was 100°C, and then cooled to room temperature, and the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, and cooled and drawn into granules. Wherein, the twin-screw processing temperature was 140-160°C, and the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0090] Example 3

[0091] 30g of PHB, 5g of P3HB4HB (4HB molar content 10%), 35g of bamboo powder, 5g of talc, 10g of calcium carbonate, 1g of silane coupling agent KH550, 2g of titanate coupling agent TCA-KTTS, 1g of BASF ADR 4468, 4g of low molecular weight PHB, 3g of calcium stearate, 2g of anti-hydrolysis agent, and 2g of antioxidant CYANOX 1010 were weighed, added into a high-speed mixer and mixed for 25min, the high-speed mixer temperature was 100°C, then cooled to room temperature, the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, cooled and drawn into granules. Wherein, the twin-screw processing temperature was 140-160°C, and the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0092] Example 4

[0093] 20g of PHB, 10g of P3HB4HB (4HB molar content 10%), 45g of bamboo powder, 2.9g of whiskers, 10g of kaolin, 2g of silane coupling agent KH550, 3g of titanate coupling agent TCA-KTTS, 0.1g of BASF ADR 4468, 5g of low molecular weight PHB, 0.5g of calcium stearate, 0.5g of anti-hydrolysis agent, and 1g of antioxidant CYANOX 1010 were weighed, added into a high-speed mixer and mixed for 25min, the high-speed mixer temperature was 100°C, then cooled to room temperature, the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, cooled and drawn into granules. Wherein, the twin-screw processing temperature was 140-160°C, and the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0094] Example 5

[0095] 30g of PHB, 5g of P3HB4HB (4HB molar content 10%), 35g of bamboo powder, 5g of talc, 10g of calcium carbonate, 3g of maleic anhydride grafted polyethylene, 1g of oxazoline type chain extender BOZ (2,2-bis-(2-oxazoline)), 4g of low molecular weight fully degradable polyester, 3g of calcium stearate, 2g of anti-hydrolysis agent, 2g of antioxidant CYANOX 1010 were weighed, added into a high-speed mixer and mixed for 25min, the high-speed mixer temperature was 100°C, then cooled to room temperature, the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, cooled and drawn into granules. Wherein, the twin-screw processing temperature was 140-160°C, the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0096] Example 6

[0097] 20g of PHB, 10g of P3HB4HB (4HB molar content 10%), 45g of bamboo powder, 2.9g of whiskers, 10g of kaolin, 5g of aluminate coupling agent DL-411, 0.1g of isocyanate chain extender diphenylmethane diisocyanate, 5g of low molecular weight fully degradable polyester, 0.5g of calcium stearate, 0.5g of anti-hydrolysis agent, 1g of antioxidant CYANOX 1010 were weighed, added into a high-speed mixer and mixed for 25min, the high-speed mixer temperature was 100°C, then cooled to room temperature, the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, cooled and drawn into granules. Wherein, the twin-screw processing temperature was 140-160°C, the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0098] Example 7

[0099] 30g of PHB, 5g of P3HB4HB (4HB molar content 10%), 35g of bamboo powder, 5g of talc, 10g of calcium carbonate, 1g of silane coupling agent SCA-V71E, 2g of titanate coupling agent TCA-KTTS, 1g of diisopropylbenzene peroxide, 4g of low molecular weight fully degradable polyester, 3g of calcium stearate, 2g of anti-hydrolysis agent, and 2g of antioxidant CYANOX 1010 were weighed, added into a high-speed mixer and mixed for 25min, the high-speed mixer temperature was 100°C, then cooled to room temperature, the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, cooled and drawn into granules. Wherein, the twin-screw processing temperature was 140-160°C, and the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0100] The polyhydroxyalkanoate bamboo powder composite material was tested using the test method of Example 1, and the results are shown in Table 2.

[0101] Comparative Example 1

[0102] 48.75g of PHB, 48.75g of bamboo powder, 2g of silane coupling agent SCA-V71E, and 0.5g of antioxidant CYANOX 1010 were weighed and added into a high-speed mixer for mixing for 25 minutes, the temperature of the high-speed mixer was 100°C, and then cooled to room temperature, and the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, and cooled and drawn into granules. The twin-screw processing temperature was 140-160°C, and the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0103] Comparative Example 2

[0104] 45g of PHB, 40g of bamboo powder, 5g of talc, 5g of calcium carbonate, 0.5g of silane coupling agent SCA-V71E, 0.5g of titanate coupling agent TCA-KTTS, 0.5g of BASF ADR 4468, 1.5g of low molecular weight PHB, 1.0g of calcium stearate, 0.5g of anti-hydrolysis agent, and 0.5g of antioxidant CYANOX 1010 were weighed and added into a high-speed mixer for mixing for 25 minutes, the temperature of the high-speed mixer was 100°C, and then cooled to room temperature, and the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, and cooled and drawn into granules. Wherein, the twin-screw processing temperature was 140-160°C, and the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0105] Comparative Example 3

[0106] 45g of PHB, 40g of bamboo powder, 5.5g of talc, 5g of calcium carbonate, 0.5g of silane coupling agent SCA-V71E, 0.5g of titanate coupling agent TCA-KTTS, 1.5g of low molecular weight PHB, 1.0g of calcium stearate, 0.5g of anti-hydrolysis agent, and 0.5g of antioxidant CYANOX 1010 were weighed and added into a high-speed mixer for mixing for 25 minutes, the temperature of the high-speed mixer was 100°C, and then cooled to room temperature, and the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, and cooled and drawn into granules. Among them, the twin-screw processing temperature was 140-160°C, and the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0107] Comparative Example 4

[0108] 45g of PHB, 40g of bamboo powder, 6.5g of talc, 5g of calcium carbonate, 0.5g of silane coupling agent SCA-V71E, 0.5g of titanate coupling agent TCA-KTTS, 0.5g of BASF ADR 4468, 1.0g of calcium stearate, 0.5g of anti-hydrolysis agent, and 0.5g of antioxidant CYANOX 1010 were weighed and added into a high-speed mixer for mixing for 25min, the temperature of the high-speed mixer was 100°C, and then cooled to room temperature, and the obtained mixture was put into a twin-screw extruder for melt blending and extrusion, and cooled and stranded for granulation. Wherein, the twin-screw processing temperature was 140-160°C, and the screw speed was 250rpm, and polyhydroxyalkanoate bamboo powder composite material granules were prepared.

[0109] The performance test results of Examples 1-7 and Comparative Examples 1-4 are shown in Table 2.

[0110] Table 2 Performance test results

[0111]

[0112]

[0113] As shown in Table 2, the polyhydroxyalkanoate bamboo powder composite materials prepared in Examples 1-7 have a melt index of more than 10 g / 10 min, a tensile strength of more than 18 MPa, a tensile elongation at break greater than 30%, and an Izod notched impact strength of 2.4 kJ / m 2 Compared with Comparative Example 1, the amount of polyhydroxyalkanoate used in Examples 1-7 is reduced. Through formula optimization, the comprehensive performance of the polyhydroxyalkanoate bamboo powder composite material is not only not reduced, but improved, thereby reducing the production cost of the material.

[0114] Compared with Examples 5-7, Examples 1-4 can further improve the comprehensive performance of the polyhydroxyalkanoate bamboo powder composite material through further optimization of the formula.

[0115] Compared with Example 1, Comparative Example 2 did not add P3HB4HB, and the tensile elongation at break was significantly reduced; Comparative Example 3 did not add a chain extender, and the tensile elongation at break and the notched cantilever beam impact strength were significantly reduced; Comparative Example 4 did not add a lubricant, and the melt index and tensile elongation at break were significantly reduced.

[0116] Therefore, the present application adopts the blending of polyhydroxyalkanoates and bamboo powder, and improves the melt index, tensile strength, tensile elongation at break and cantilever beam notched impact strength of the composite material through formula design, improves the mechanical properties and processing properties of the composite material, improves the comprehensive performance of polyhydroxyalkanoates, overcomes the disadvantage of slow crystallization rate of polyhydroxyalkanoates, while maintaining the biodegradability of polyhydroxyalkanoates, and reduces the amount of polyhydroxyalkanoates, thereby greatly reducing costs.

[0117] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A polyhydroxyalkanoate bamboo powder composite material, characterized in that: The invention comprises the following raw materials in weight percentage: 30-45% polyhydroxyalkanoate, 30-45% bamboo powder, 1-15% filler, 0.1-5% coupling agent, 0.1-1% chain extender, 0.1-5% lubricant, 0.1-5% heat stabilizer, 0.1-2% anti-hydrolysis agent and 0.1-2% antioxidant; wherein the polyhydroxyalkanoate comprises PHB and P3HB4HB.

2. The polyhydroxyalkanoate bamboo powder composite material according to claim 1, wherein: Based on the weight of the polyhydroxyalkanoate bamboo powder composite material as 100%, the polyhydroxyalkanoate includes 20-40% PHB and 5-20% P3HB4HB, preferably the polyhydroxyalkanoate includes 20-30% PHB and 5-20% P3HB4HB; preferably, the molar content of 4HB in the P3HB4HB is 5-20%; more preferably, the weight average molecular weight of the PHB is 50-90w, and the weight average molecular weight of the P3HB4HB is 50-90w.

3. The polyhydroxyalkanoate bamboo powder composite material according to claim 1 or 2, wherein: The polyhydroxyalkanoate is 40-45%; and / or the bamboo powder is 30-40%.

4. The polyhydroxyalkanoate bamboo powder composite material according to any one of claims 1 to 3, wherein: The filler is 10-15%; and / or, The coupling agent is 1-5%, preferably 1-2%; and / or, The chain extender is 0.5-1%; and / or, The lubricant is 1.5-5%, preferably 1.5-3%; and / or, The thermal stabilizer is 0.5-5%, preferably 1-5%; and / or, The anti-hydrolysis agent is 0.5-2%; and / or, The antioxidant is 0.5-2%.

5. The polyhydroxyalkanoate bamboo powder composite material according to any one of claims 1 to 4, wherein: The coupling agent includes one or more of maleic anhydride coupling agent, titanate coupling agent, aluminate coupling agent and silane coupling agent; preferably, titanate coupling agent and silane coupling agent, more preferably, the mass ratio of the titanate coupling agent to the silane coupling agent is 0.5-3:0.5-2, preferably 0.5-1:0.5-1.

6. The polyhydroxyalkanoate bamboo powder composite material according to any one of claims 1 to 5, wherein: The chain extender includes one or more of epoxy functional group chain extender, oxazoline type chain extender, isocyanate chain extender and peroxide; preferably, the epoxy functional group chain extender.

7. The polyhydroxyalkanoate bamboo powder composite material according to any one of claims 1 to 6, wherein: The lubricant comprises low molecular weight fully degradable polyester and / or low molecular weight polyhydroxyalkanoate.

8. The polyhydroxyalkanoate bamboo powder composite material according to any one of claims 1 to 7, wherein: The heat stabilizer comprises one or more of calcium stearate, zinc stearate, nanocellulose, nano-montmorillonite and fumed silica, preferably calcium stearate and / or zinc stearate; and / or, The anti-hydrolysis agent includes carbodiimides; and / or, The filler comprises one or more combinations of talc, calcium carbonate, whiskers or kaolin, preferably calcium carbonate and talc; and / or, The antioxidant includes one or more of hindered phenols, phosphates, phosphites and aromatic amines, preferably hindered phenols and / or phosphates.

9. The method for preparing the composite material according to any one of claims 1 to 8, characterized in that: It includes the following steps: (1) mixing, heating and mixing the raw materials, and cooling to obtain a mixed material; (2) Granulation: granulating the mixed material obtained in step (1).

10. The preparation method according to claim 9, characterized in that: The heating temperature in step (1) is 100-120° C., and the preferred mixing time is 20-30 min.

11. The preparation method according to claim 9 or 10, characterized in that: The granulation in step (2) comprises adding the mixed material obtained in step (1) into a twin-screw extruder for melt blending and extrusion granulation. The extrusion temperature is preferably 140-160° C., and the rotation speed is more preferably 200-350 rpm.

12. The preparation method according to any one of claims 9 to 11, characterized in that: The preparation method further comprises the step of molding the particles obtained in step (2), preferably molding the particles obtained in step (2) by extrusion, injection molding, casting or die casting.

Citation Information

Patent Citations

  • Bamboo-based degradable composite material for injection molding and preparation method thereof

    CN106832831A

Cited By

  • PLA-PHA bamboo-plastic composite material and preparation method thereof

    CN121517875A